Living with uncertainty social change and the Vietnamese family in the rural Mekong Delta - Shibuya, Setsuko 1966- (Institute of Southeast Asian Studies, 2015)
This is one of the first ethnographies written on the life of farmers in rural Southern Vietnam since the economic reform in the 1980s. It investigates how social, economic and political factors affect the farmers' life in the Mekong Delta in the late socialist era, with a particular focus on the family, which serves as the basic and most significant social unit for the farmers.